Problem Based Learning Sebagai Strategi Penting untuk Mengajar Ilmu Pengetahuan Alam di Kelas V (Materi IPA Kelas V Sekolah Dasar) - Ulfah Ulfiya Nur Ramadhanty; Heri Yusuf Muslihin (Departement of Mathematics Education, 2024)
This research is motivated by the large number of students who are not used to using their reasoning powers but instead are used to memorizing, only fixate on source books, and feel that there is a gap between learning in the classroom and the students' daily life environment. For this reason, it is necessary to strive for science learning that emphasizes a culture of critical thinking that provides nuances of technology, environment, and society, as well as science learning that refers to the future, so that competent students are produced. In the 21st century, education demands the participation of students who are able to face global economic competition. The Partnership for 21st Century Skills emphasizes that 21st century learning must teach four competencies, namely communication, collaboration, critical thinking, and creativity. The learning process through the problem-based learning model can certainly familiarize students with developing their' critical thinking skills. Problem-based learning is curriculum development with a teaching system that stimulates the development of problem-solving strategies and basic knowledge and skills by placing students in an active role as solvers of everyday problems that are not well structured. The ability of students to understand the solar system and the characteristics of the members of the solar system in Exploring Space (Theme 9) Amazing regularity (sub-theme 9) The science content is not yet optimal, causing students to feel bored with the learning system, which is still very monotonous, so that the results obtained are not yet as expected. From these results, problem-based learning is very influential on science learning in Grade 5 elementary schools. Therefore, problem-based learning can be used in teaching strategies for natural science at the Grade V elementary school level.